Learning from Noise? Price and Liquidity Spillovers around Mutual Fund Fire Sales - Honkanen, Pekka; Schmidt, Daniel (The Review of Asset Pricing Studies, 2022)
Abstract We study the extent of cross-asset learning in financial markets by examining the spillover effects around mutual fund fire sales, which lead to a well-documented impact-reversal pattern in returns. We find that the returns of fire sale stocks spill over onto the stock returns of economic peers with a magnitude of around one-third of the original effect. These spillovers extend to liquidity and are not explained by common funding shocks or the hedging activity of liquidity providers. We conclude that they represent information spillovers due to learning from prices, thus identifying cross-asset learning as an important driver for the commonality in returns and liquidity. (JEL G11, G12, G14, G23) Received July 1, 2021; editorial decision August 30, 2021. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.